Breaking the cellular defense: the role of autophagy evasion in Francisella virulence - Pavla Pavlik; Pavla Pavlik; Eva Velecka; Petra Spidlova (Frontiers in Cellular and Infection Microbiology)
Many pathogens have evolved sophisticated strategies to evade autophagy, a crucial cellular defense mechanism that typically targets and degrades invading microorganisms. By subverting or inhibiting autophagy, these pathogens can create a more favorable environment for their replication and survival within the host. For instance, some bacteria secrete factors that block autophagosome formation, while others might escape from autophagosomes before degradation. These evasion tactics are critical for the pathogens’ ability to establish and maintain infections. Understanding the mechanisms by which pathogens avoid autophagy is crucial for developing new therapeutic strategies, as enhancing autophagy could bolster the host’s immune response and aid in the elimination of pathogenic bacteria. Francisella tularensis can manipulate host cell pathways to prevent its detection and destruction by autophagy, thereby enhancing its virulence. Given the potential for F. tularensis to be used as a bioterrorism agent due to its high infectivity and ability to cause severe disease, research into how this pathogen evades autophagy is of critical importance. By unraveling these mechanisms, new therapeutic approaches could be developed to enhance autophagic responses and strengthen host defense against this and other similarly evasive pathogens.